2016
DOI: 10.1007/s10955-016-1539-3
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Investigation into Near Degenerate Exponential Random Graphs

Abstract: The exponential family of random graphs has been a topic of continued research interest. Despite the relative simplicity, these models capture a variety of interesting features displayed by large-scale networks and allow us to better understand how phases transition between one another as tuning parameters vary. As the parameters cross certain lines, the model asymptotically transitions from a very sparse graph to a very dense graph, completely skipping all intermediate structures. We delve deeper into this ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The complete clique is simply no longer an allowed configuration, and hence the number of triangles becomes fully tuneable, if the model parameters scale appropriately with the system size. In addition, in [25] it is shown that the 'soft' version of our model would have a phase diagram reminiscent of ours. In both cases the sign of a linear combination of functions of the parameters determines the phase of the ensemble.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The complete clique is simply no longer an allowed configuration, and hence the number of triangles becomes fully tuneable, if the model parameters scale appropriately with the system size. In addition, in [25] it is shown that the 'soft' version of our model would have a phase diagram reminiscent of ours. In both cases the sign of a linear combination of functions of the parameters determines the phase of the ensemble.…”
Section: Discussionsupporting
confidence: 53%
“…This abrupt transition was found to be a generic feature of exponential random graph models. As was shown in [24,25], this phenomenon will be observed not only in twoparameter models like the Strauss model, but in any exponential graph ensemble that is biased such as to induce a finite number of subgraph densities.…”
Section: Introductionmentioning
confidence: 70%
“…The theory of graph limits developed by Lovász and coauthors [22] has received phenomenal attention over the last few years. It connects various topics such as graph homomorphisms, Szemeredi's regularity lemma, and quasirandom graphs, and has found many interesting applications in statistical physics, extremal graph theory, statistics and related areas (see [5,6,13,25,26,29,30] and the references therein). Here we recall the basic definitions about the convergence of graph sequences.…”
Section: 21mentioning
confidence: 99%
“…exponential ensemble of [10]. Unfortunately, upon varying the control parameters this ensemble was found to switch between very weak clustering and dominance by dense graphs [11][12][13]. See also [14].…”
Section: Introductionmentioning
confidence: 99%